2016
DOI: 10.1038/srep35115
|View full text |Cite|
|
Sign up to set email alerts
|

Arabidopsis aldehyde dehydrogenase 10 family members confer salt tolerance through putrescine-derived 4-aminobutyrate (GABA) production

Abstract: Polyamines represent a potential source of 4-aminobutyrate (GABA) in plants exposed to abiotic stress. Terminal catabolism of putrescine in Arabidopsis thaliana involves amine oxidase and the production of 4-aminobutanal, which is a substrate for NAD+-dependent aminoaldehyde dehydrogenase (AMADH). Here, two AMADH homologs were chosen (AtALDH10A8 and AtALDH10A9) as candidates for encoding 4-aminobutanal dehydrogenase activity for GABA synthesis. The two genes were cloned and soluble recombinant proteins were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 44 publications
0
42
0
Order By: Relevance
“…4.1.1.15) in the cytosol. An alternative pathway from polyamines to GABA is catalyzed by copper‐containing amine oxidases (Fincato et al ., ; Planas‐Portell et al ., ) and/or FAD‐dependent amine oxidases followed by aminoaldehyde dehydrogenases (ALDH10 family; Tylichová et al ., ; Kopečný et al ., ; Zarei et al ., ). Once GABA enters mitochondria, it is converted to SSAL via a GABA transaminase (GABA‐T; E.C.…”
Section: Resultsmentioning
confidence: 97%
“…4.1.1.15) in the cytosol. An alternative pathway from polyamines to GABA is catalyzed by copper‐containing amine oxidases (Fincato et al ., ; Planas‐Portell et al ., ) and/or FAD‐dependent amine oxidases followed by aminoaldehyde dehydrogenases (ALDH10 family; Tylichová et al ., ; Kopečný et al ., ; Zarei et al ., ). Once GABA enters mitochondria, it is converted to SSAL via a GABA transaminase (GABA‐T; E.C.…”
Section: Resultsmentioning
confidence: 97%
“…Arabidopsis does not produce 5‐aminopentanal or 5‐aminopentanoate but rather produces analogs that are one carbon atom shorter: 4‐aminobutanal and GABA, respectively. The conversion of 4‐aminobutanal to GABA was previously shown to be catalyzed by AtALDH10A8 and AtALDH10A9 (Missihoun et al ., ; Stiti et al ., ; Zarei et al ., ). In this study, we functionally characterized AtALDH10A8 and AtALDH10A9 enzymes and showed that both enzymes could catalyze the conversion of 5‐aminopentanal to 5‐aminopentanoate.…”
Section: Discussionmentioning
confidence: 97%
“…The full-length cDNA clones of AtALDH10A8 and AtALDH10A9 were obtained from RIKEN BioResource Research Center (https://ja.brc.riken.jp) (pda07810 and pda01165, respectively). Vector construction and the expression of recombinant protein followed by affinity purification were conducted as described previously (Zarei et al, 2016). The reaction mixture for the AtALDH10A8 functional assay consisted of 30 mM Tris-HCl buffer (pH 8.5), 0.1 mM NAD + and 1 mM 5-aminopentanal, whereas the reaction mixture for AtALDH10A9 functional characterization contained 30 mM N-cyclohexyl-2aminoethanesulfonic acid buffer (pH 9.5), 0.5 mM NAD + and 1 mM 5-aminopentanal.…”
Section: Functional Assay Using Recombinant Ataldh10a8 and Ataldh10a9mentioning
confidence: 99%
“…It has been also reported that ataldh10A8 and ataldh10A9 T-DNA-insertion mutants reduced GABA accumulation than wild-type plants of A. thaliana during salinity treatment and are more sensitive to salinity stress. [33] GABA-T and GAD are the key enzymes in GABA-shunt pathway. Enzymes activities of these enzymes were assayed at different leaf developmental stages in wild-type and pop2-3 mutant plant and compared with GABA-T complement plant.…”
Section: Discussionmentioning
confidence: 99%